The Dragon in The Lion’s Nest: Confucianism Under The Colonial Legal System - Juwono, Harto (Mandarinable: Journal of Chinese Studies, 2025)
This article aims to reveal the position and status of Confucianism under the colonial legal system in the Dutch East Indies. By explaining this status, this article not only provides an explanation of the religion as a legal entity but also the limitations of its rights and obligations, including ownership rights over land used for its liturgical and social activities. For that, with a temporal scope of the colonial era, the method used to construct it is the historical method combined with the methodology of legal science. Through a combination of the two, it is hoped that this paper will be useful to provide explanations at least to the scholars from both disciplines. The data used in this research is colonial-era data, which consists of archival sources (especially manuscript) and contemporaneous information sources (old newspapers). The use of such data is based on the consideration that the information obtained has a high value of validity and legality and supports the objective judgements contained in the conclusions. The conclusion of this research is that there was a dualism within the colonial policy, between viewing Confucianism as a legitimate form of religion like other religions or making Confucianism an integral legal part of the Chinese community.